FRI0434 TIE2 As a Novel Key Factor of Microangiopathy in Systemic Sclerosis. (9th June 2015) - Maurer, B.; Moritz, F.; Distler, J.H.; Michel, B.A.; Gay, R.E.; Gay, S.; Distler, O.
Abstract : Background: The angiopoietin (ang)/Tie2 system is a key regulator of vascular biology. However, its impact on SSc-associated microangiopathy has not yet been addressed in detail. Objectives: To assess the role of ang/Tie2 in SSc-associated dermal microangiopathy ex vivo and in four different animal models. Methods: The expression of Ang1/2 and Tie2 in the serum/dermis of SSc patients (n=24/10) was compared with healthy donors (n=20/8) by ELISA/immunohistochemistry (IHC). Hypoxia exposed C57BL/6 mice (n=3) were compared with normoxic controls (n=9). Mono- and double (n=9/8) VEGF transgenic (tg) mice were compared with wild type controls (n=6/9). The impact of inflammatory and non-inflammatory conditions were evaluated in the bleomycin and TSK1 model (n=4 each). For statistical analysis, GraphPad Prism software was employed. Parametric non-related data were expressed as mean ± SEM, nonparametric non-related data as median(Q1, Q3) . P-values <0.05 were considered statistically significant. Results: In dermal microvessels of SSc patients Ang2, but not Ang1 was more abundantly expressed compared with healthy controls (p=0.004) indicating vessel destabilizing conditions. Most interestingly, in SSc, membrane bound (mb) Tie2 was nearly undetectable in dermal microvessels (p<0.001). Tie2+ microvessels occurred in 90% of healthy controls but only in 5.5% of SSc patients. In context with the remarkably lower microvascular density in SSc patients (p=0.05), this supports previous observations that deficiency of Tie2 protein results in microvasculopathy. To evaluate whether the loss of mbTie2 might be due to shedding, we assessed the serum levels of soluble (s) Tie2. Interestingly, sTie2 levels of SSc patients were higher than those of healthy controls (p=0.001). As in skin, the ang1/ang2 ratio was substantially reduced in SSc sera (p<0.001). These findings suggest that the competitive binding of sTie2 and Ang2 prevents Tie2 activation with anti-angiogenic effects. Next, we evaluated the in vivo effects of angiogenic factors on the expression of ang/Tie2. In VEGF tg mice, similar to SSc, reduction of mbTie2 (p=0.002), increase of Ang2 (p=0.05) and decrease of Ang1 (p=0.07) occurred in the dermis. These results indicate that a dysregulation of ang/Tie2 might contribute to the anti-angiogenic effects of chronically elevated VEGF levels in SSc. In the hypoxia model, Tie2-mRNA was increased (p=0.042) which underlines that chronic hypoxia and VEGF exposure induce reduction of Tie2 protein by shedding. Similar to VEGF tg mice, the reduced Ang1/Ang2 ratio in the hypoxia model indicated anti-angiogenic effects. In the bleomycin model, the pro-inflammatory conditions had no effect on the dermal expression ang/Tie2. Interestingly, in the TSK1 model, our findings supported interactions of extracellular matrix (ECM) and angiogenesis. Membrane bound Tie2 was increased (p<0.0001) whereas Ang1/2 were decreased which is in line with previous studies showing that α5β1 integrin activates Tie2 at low Ang-1 concentrations. Conclusions: Our data derived from SSc patients and 4 different SSc animal models give evidence of an alteration of the ang/Tie2 system towards vessel destabilization in which VEGF, hypoxia and ECM interactions might play a major role. Disclosure of Interest: B. Maurer: None declared, F. Moritz Grant/research support from: Articulum Fellowship Pfizer, Speakers bureau: Roche, Lilly, Medac, J. Distler: None declared, B. Michel: None declared, R. Gay: None declared, S. Gay: None declared, O. Distler Grant/research support from: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation.